Ras/MAPK dysregulation in development causes a skeletal myopathy in an activating BrafL597V mouse model for cardio‐facio‐cutaneous syndrome. Issue 8 (13th February 2021) - Maeda, Yoshiko; Tidyman, William E.; Ander, Bradley P.; Pritchard, Catrin A.; Rauen, Katherine A.
Abstract: Background: Cardio‐facio‐cutaneous (CFC) syndrome is a human multiple congenital anomaly syndrome that is caused by activating heterozygous mutations in either BRAF, MEK1, or MEK2, three protein kinases of the Ras/mitogen‐activated protein kinase (MAPK) pathway. CFC belongs to a group of syndromes known as RASopathies. Skeletal muscle hypotonia is a ubiquitous phenotype of RASopathies, especially in CFC syndrome. To better understand the underlying mechanisms for the skeletal myopathy in CFC, a mouse model with an activating Braf L597V allele was utilized. Results: The activating Braf L597V allele resulted in phenotypic alterations in skeletal muscle characterized by a reduction in fiber size which leads to a reduction in muscle size which are functionally weaker. MAPK pathway activation caused inhibition of myofiber differentiation during embryonic myogenesis and global transcriptional dysregulation of developmental pathways. Inhibition in differentiation can be rescued by MEK inhibition. Conclusions: A skeletal myopathy was identified in the CFC Braf L597V mouse validating the use of models to study the effect of Ras/MAPK dysregulation on skeletal myogenesis. RASopathies present a novel opportunity to identify new paradigms of myogenesis and further our understanding of Ras in development. Rescue of the phenotype by inhibitors may help advance the development of therapeutic options for RASopathy patients. Key Findings: A novel CFC mouse model harboring a heterozygous BrafL597V mutation caused a skeletal myopathy characterized by an inhibition of myogenesis during embryonic development and a reduction in skeletal muscle mass and strength due to an overall reduction in muscle fiber size. The BrafL597V mutation not only caused activation of the Ras/MAPK pathway, but also resulted in inhibition of the critical p38 pathway. Therefore, the overall skeletal myopathy resulted from the combined effect of dysregulation of both of these pathways and emphasizes the integrative role they play during skeletal muscle development. The use of this novel mouse model provides insight into the underlying cause of the skeletal myopathy in CFC individuals and other RAS opathies, but also provides detail of the role of the Ras/MAPK pathway in skeletal muscle development. The use of this CFC mouse model lends itself to determining the feasibility of developmentally correcting the skeletal myopathy by prenatal administration of a MEK inhibitor as well as to whether aspects of the abnormal muscle phenotype can be rescued by postnatal MEK inhibitor treatment. These data will help guide us in the development of rational therapeutic options to treat RASopathies, as well as being applicable to future studies regarding the function of the Ras/MAPK pathway in other skeletal muscle wasting disorders including muscular dystrophies and sarcopenia.